Ambush Marketing: Blessing Or Curse - Chawla, Nitish (Gyan Management Journal, 2020)
The article gives an insight into the marketing of ambushes; this type of marketing has a different  aspect to the marketing strategies used by companies. It is commonly used for companies facing a high  degree of competition. The  accompanying  report  presents  readers  with  extensive  details  on the  methods  used,  forms  of  ambush marketing, their  evolution,  various  viewpoints  on their  usage,  laws  and  regulations,  and  ethical beliefs and  expectations. The article also gives  examples of the ambush marketing and its  effects, pros and cons by companies. Events around the world may have led to laws concerning ambush  marketing, but in India, despite a number of activities in ambush marketing in India, there is no specific  law dealing with ambush marketing. The article focuses on embassy tactics, the effect of these actions  on sponsors, event managers and consumers as well as regulations to discourage such practices.
Keywords: AMBUSH MARKETING; WHETHER A BLESSING OR CURSE -FOR A BUSINESS